THE ROLE OF IPS LEARNING IN SHAPING STUDENTS' CRITICAL UNDERSTANDING OF THE COMMODIFICATION OF BELIS CULTURE IN MANGGARAI - Femberianus Sunario Tanggur; Hamdan Tri Atmaja; I G W Wisnuwardana; Saddam Saddam; Nuryanti Nuryanti (Universitas Citra Bangsa, 2025)
ABSTRACT This research aims to analyze the role of Social Studies learning in shaping students' critical understanding of the phenomenon of commodification of Belis culture in Manggarai. The method used was a qualitative approach with a case study design, involving 132 students at SMP Negeri 9 Borong, East Manggarai, as well as teachers and the surrounding community. Data were collected through in-depth interviews, observation, and documentation, and analyzed using thematic analysis. The main findings of this study show that social studies learning plays an important role in raising students' social awareness of the phenomenon of commodification of Belis culture. Although most students understand the culture of Belis, they do not fully understand the social and economic impacts of changing the form of Belis, from livestock to money. Social studies learning is able to stimulate students' critical thinking, but there are still gaps in their understanding of the wider implications of commodification on the cultural values and social structure of Manggarai society. In conclusion, social studies learning needs to be adapted to the local context to be more relevant to social and cultural conditions, as well as to encourage students to think more critically and actively in preserving Belis culture in the midst of changing times.